Studi Deskriptif Pengetahuan Remaja Mengenai Menarche sebagai Tanda Pubertas - Yustanta, Brivian Florentis (STIKES dan AKZI Karya Husada Kediri, 2026)
Puberty is the stage where the sexual organs have matured, marked by the ability to reproduce. During this period, teenage girls can experience menarche or their first menstruation due to hormonal changes that occur in women. The lack of readiness of young women to face menarche can make young women afraid, anxious, embarrassed and confused. The readiness of young women to face menarche needs to be assisted by providing information from parents, teachers, midwives or cadres. The aim of this research is to determine the level of knowledge possessed by teenagers in dealing with menarche at elementary school Class 6 Muhamadiyah Ambon. The research method is descriptive. The research was carried out from 14 to 21 October 2024 at grade 6 elementary school Muhamadiyah Ambon, using a total sampling technique from a population of 30 respondents. The instrument in this research uses a questionnaire with data collection techniques filled in by the respondents themselves, the data is collected and processed by the researcher. Based on the research results, the majority of 18 people (60%) from the distribution of respondents' characteristics based on knowledge were female students with good knowledge, almost half of them 8 (26.6%) female students had sufficient knowledge and a small number of 4 people (13.4%) had poor knowledge. The knowledge a person has will determine a person's behavior. Teenagers' knowledge needs to be developed through the surrounding environment such as parents, teachers and the role of health workers to increase teenagers' knowledge about preparing for menarche and how to deal with menarche